2016
DOI: 10.1681/asn.2014121264
|View full text |Cite
|
Sign up to set email alerts
|

Blocking rpS6 Phosphorylation Exacerbates Tsc1 Deletion–Induced Kidney Growth

Abstract: The molecular mechanisms underlying renal growth and renal growth-induced nephron damage remain poorly understood. Here, we report that in murine models, deletion of the tuberous sclerosis complex protein 1 (Tsc1) in renal proximal tubules induced strikingly enlarged kidneys, with minimal cystogenesis and occasional microscopic tumorigenesis. Signaling studies revealed hyperphosphorylation of eukaryotic translation initiation factor 4E-binding protein 1 (4E-BP1) and increased phosphorylation of ribosomal prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 76 publications
(98 reference statements)
0
22
0
Order By: Relevance
“…11,13,[18][19][20][21] To investigate whether IL-17C activated Th17 in AKI, we assessed Th17 cell quantity in the kidney using co-staining for CD4 and IL-17A as described previously. 22,23 The results showed that renal Th17 cell quantity was increased, whereas the numbers were decreased significantly by an IL-17C-neutralizing antibody or IL-17RE knockout in mice with IRI ( Figure 6a and b). IL-17A, mainly produced by Th17, was increased in the kidney of AKI mice, and it was decreased remarkably by an IL-17Cneutralizing antibody or IL-17RE knockout (Figure 6c).…”
Section: Il-17c Inhibition and Il-17re Knockout Attenuated Th17 Activmentioning
confidence: 99%
See 1 more Smart Citation
“…11,13,[18][19][20][21] To investigate whether IL-17C activated Th17 in AKI, we assessed Th17 cell quantity in the kidney using co-staining for CD4 and IL-17A as described previously. 22,23 The results showed that renal Th17 cell quantity was increased, whereas the numbers were decreased significantly by an IL-17C-neutralizing antibody or IL-17RE knockout in mice with IRI ( Figure 6a and b). IL-17A, mainly produced by Th17, was increased in the kidney of AKI mice, and it was decreased remarkably by an IL-17Cneutralizing antibody or IL-17RE knockout (Figure 6c).…”
Section: Il-17c Inhibition and Il-17re Knockout Attenuated Th17 Activmentioning
confidence: 99%
“…27,45 Co-staining of CD4 and IL-17A was used to identify Th17 cells in the kidney, as described previously. 22,23 Regulatory T cells were identified using FOXP3 staining. 48 The number of CD4 þ /IL-17A þ cells or FOXP3 þ cells was quantified by analysis of 20 randomly chosen fields.…”
Section: Evaluation Of Oxidative Stressmentioning
confidence: 99%
“…Currently, mTORC1 is considered a pharmacological target for the treatment of TSC 7,10 . Unfortunately, mTORC1 inhibitors currently used in the clinic seemed to only have a limited cytostatic effect, as the TSC tumors grew again after mTORC1 inhibitors were discontinued, and long-term mTORC1 inhibition could cause detrimental side effects [11][12][13][14][15] . It is noteworthy that deletion of human TSC2 and PKD1 genes results in severe infantile polycystic kidney disease (PKD)-a contiguous gene syndrome 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Neither sirolimus (rapamycin) nor everolimus (sirolimus analog) is effective in treating PKD, and these drugs have been reported to cause albuminuria (caused by sirolimus) and leukopenia (caused by everolimus) [16][17][18] . Moreover, our previous study demonstrated that either pharmacologic inhibition of mTORC1 or genetic deletion of rpS6 phosphorylation exacerbated structural and functional damage of the kidneys in Tsc1 gene-deleted mice 11 , suggesting that alternative strategies are needed for effective treatment of TSC-associated kidney disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation